PECULIARITIES OF VARIABLES REPLACEMENT IN THE RIEMAN INTEGRAL IN THE MATHEMATICAL ANALYSIS COURSE IN FUTURE TEACHERS OF MATHEMATICS TRAINING - Samoylenko, V.; Hryhorieva, V.; Hniedkova, O.; Kotova, O. (Physical and Mathematical Education, 2021)
The article considers the peculiarities of variables substitution introduction in the Riemann integral in the teaching of mathematical analysis in pedagogical specialties of higher educational institutions. Problem formulation. Due to the fact at present secondary and vocational education have entered a fundamentally new stage of its development, the characteristic features of which are the development of education on the basis of new progressive concepts, the introduction into the educational process of modern pedagogical and information technologies, scientific methodological achievements, the problem of improvement of the professional training of mathematics teachers is especially relevant. Mathematical analysis has a great importance in future mathematics teachers learning. The article on the example of consideration of a specific issue of this course identifies the mathematical aspects related to the peculiarities of material teaching, taking into account the current requirements for learning process. The question of replacing variables in the Riemann integral for functions given on metric spaces with measure, in particular, in multiple integrals, is considered. Materials and methods. General methods of mathematical analysis and analysis of mathematical literature on the calculation of multiple integrals and the Riemann integral using the method of substituting variables, analysis and generalization of own pedagogical experience and pedagogical experience of leading teachers and scientists were used. Results. The paper considers the author's approach to replacement of variables in the integral in the general case, the replacement of variables in the Riemann integral by a segment, as well as for multiple integrals of functions given on metric spaces with measure. Conclusions. The approach discussed in the article has certain advantages, which are explained by the fact that multiples, surface and curvilinear integrals fit into this scheme and are obtained as examples with the appropriate choice of space and measure. That is why this approach in the learning of future mathematics teachers contributes to the professional orientation of teaching mathematical analysis.
Keywords: mathematical analysis; function given on a metric space with measure; Riemann integral; information technologies; variable